EXPLORATION OF STRUCTURE-SWITCHING IN THE DESIGN OF RNA APTAMER SENSORS - Lau, Pui Sai (My University, 2014)
The process of ‘‘structure-switching’’ enables biomolecular switches to function as effective biosensing tools. Biomolecular switches can be activated or inactivated by binding to a specific target that triggers a precise conformational change in the biomolecules involved. Examples of aptamer-based biomolecular switches can be found in nature. Furthermore, efforts have been made in the last decade to engineer structure-switching sensors using DNA aptamers whereby, the aptamer is coupled to a signal transduction method to generate a readout signal upon target binding to the aptamer domain. Conversely, RNA aptamers have been relatively underexplored for sensor development, largely due to its susceptibility to nuclease degradation and chemical instability. Despite these shortcomings, many RNA aptamers possess superior sensing capabilities, and the abundance of RNA aptamers provides new opportunities to further advance the field. In effect, this thesis uses a structure-switching design to demonstrate the power of RNA aptamers for fluorescence-based sensor development. Herein, we demonstrate generalizable structure-switching strategies to make use of the abundance of RNA aptamers, monitor the quality control of detection and correct detection error, as well as enhance RNA aptamer sensing capability by using regulated graphene adsorption. Furthermore, our findings have expanded for secondary applications involving collaborations with other research labs. In one application, we demonstrate that entrapment of structure-switching RNA aptamers in sol-gel material confers protection against nuclease degradation and chemical instability. In another application, we further validate the use of riboswitches, or natural structure-switching RNA aptamers, as potential targets for drug discovery. Overall, these results demonstrate the capability of RNA aptamers for sensor development. We conclude with a discussion of possible areas for further inquiry, as well as future applications for the advancement of structure-switching RNA aptamers.
Keywords: aptamer; RNA; sensor; structure-switching; fluorescence; SELEX; Other Analytical, Diagnostic and Therapeutic Techniques and Equipment; Other Analytical, Diagnostic and Therapeutic Techniques and Equipment